Plan de negocios para la producción y exportación de uvilla al mercado de Miami, Estados Unidos - Salguero Cajas, Juan Gerardo (2020)
Current consumption trends in first world countries have allowed various customs and part of the culture of third world countries to stand out and achieve a position in the market, as unique options and offering added value among the options that a customer can find. This project analyzes the profitability of a company that focuses on producing and exporting uvillas from Ecuador to the United States. For which, certain economic, social, political and technological variables have been determined that influence its development, both in Ecuador and in the United States; however, the variables in favor of the project have allowed us to deduce that the environment in which it is planned to be developed is the ideal one to obtain favorable results from it, and that it may be profitable in the future. Information was obtained that allowed us to appreciate that the project has great acceptance in the target market since the current offer does not cover the needs of customers who are looking for healthy food options. Allowing us to analyze that the business opportunity of this project lies in the possibility of offering a product with exotic qualities, in a market that is actively searching for this type of goods. Taking into account the financial results, favorable numbers were obtained that ensure the profitability of the project even in a projection of 5 years, implying it is a project in which it turns out to invest and expect positive results in the short and medium term. Thus, it is feasible, since this project will manage various resources necessary to develop in one country, and be able to extend to another without achieving losses due to the expected demand and how this will be reflected in the sales and income of the project.